A long-lasting antibacterial, thermally conductive, flame-retardant thermoplastic elastomer composite material based on TPC-ET and preparation method thereof

By introducing nano-loaded silver-particle polycyclic triphosphazene dihydroxydiphenylsulfone microspheres and other functional additives into the TPC-ET material, a long-acting antibacterial thermally retardant thermoplastic elastomer composite material was prepared, which solved the problem of insufficient thermal conductivity of TPC-ET material and achieved the improvement of high thermal conductivity, flame retardancy and mechanical properties.

CN119161701BActive Publication Date: 2025-03-14GUIZHOU MATERIAL IND TECH INSTITUE
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411501177.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-25
Publication Date
2025-03-14
Estimated Expiration
2044-10-25

AI Technical Summary

Technical Problem

TPC-ET materials have poor thermal conductivity. Adding high-thermal conductivity inorganic fillers can easily lead to increased material viscosity, uneven dispersion of fillers and interface thermal resistance, making it difficult to meet the actual application of thermal conductivity and mechanical properties.

Method used

The nano-loaded silver particles polycyclic triphosphazene dihydroxydiphenylsulfone microspheres are used as antibacterial and flame retardant, and combined with materials such as polysiloxane, low-melting glass powder, boron nitride and aluminum nitride, and long-acting antibacterial thermally retardant thermoplastic elastomer composite materials are prepared through extrusion and granulation processes.

Benefits of technology

It has achieved a coordinated improvement of high thermal conductivity, flame retardancy and mechanical properties of TPC-ET materials, and the material has improved thermal conductivity and good processing performance. It is suitable for wires, cables, electronics, medical and transportation fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005102647680000161
    Figure BDA0005102647680000161
  • Figure BDA0005102647680000171
    Figure BDA0005102647680000171
Patent Text Reader

Abstract

The present invention provides a long-lasting antibacterial, heat-conductive, flame-retardant thermoplastic elastomer composite material based on TPC-ET and a preparation method thereof, belonging to the technical field of thermoplastic elastomer composite materials. The composite material includes the following raw materials in mass percentage: 30wt% to 80wt% of thermoplastic polyester polyether elastomer copolymer; 18.5wt% to 69.5wt% of functional additives; 0.5wt% to 1.5wt% of processing aids; the functional additives are flame retardants, auxiliary flame retardants, thermal conductive fillers, compatibilizers, antibacterial agents and light stabilizers; the flame retardant is an organosilicon flame retardant; the auxiliary flame retardant is a low-melting point glass powder; the thermal conductive filler is a nitride; the antibacterial agent is a loaded nano-silver particle polycyclotriphosphazene dihydroxydiphenyl sulfone microsphere. The composite material provided by the present invention has long-lasting antibacterial, high thermal conductivity, high flame retardancy and excellent mechanical properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of thermoplastic elastomer composite materials, and in particular to a long-lasting antibacterial, heat-conductive, flame-retardant thermoplastic elastomer composite material based on TPC-ET and a preparation method thereof. Background Art

[0002] Thermoplastic polyester polyether elastomer copolymer (TPC-ET) is a linear block copolymer of polybutylene terephthalate hard segment and polyether soft segment, wherein the polyether soft segment is a non-crystalline polyether, including polyethylene glycol ether, polypropylene glycol ether, polybutylene glycol ether, etc. As a thermoplastic elastomer composite material, TPC-ET has the characteristics of both plastic and rubber, and its hardness range can be selected from Shore 28D-80D. In addition, this material is recyclable. TPC-ET has excellent toughness and elasticity, high creep resistance, impact resistance and flex fatigue resistance, flexibility at low temperature and good performance retention at high temperature. TPC-ET can still maintain more than 80% of its toughness in a low temperature environment of -40°C, which is enough to meet most low-temperature applications. In addition, it is also resistant to many industrial chemicals, oils and solvents. TPC-ET does not contain plasticizers, is non-toxic and tasteless, and meets the hygiene standards of food and medicine. However, TPC-ET itself does not have flame retardant properties, and it needs to be flame retardant modified in some applications.

[0003] With the vigorous development of 5G communication technology, electronic components are becoming increasingly miniaturized, integrated, and high-power, resulting in a significant increase in the heat generated by the equipment. How to quickly dissipate heat from the equipment has become a key issue that needs to be solved. However, for TPC-ET, its own thermal conductivity is about 0.15W / (m·K), and its thermal conductivity is poor. Therefore, a large amount of high thermal conductivity inorganic fillers such as alumina, aluminum nitride, and boron nitride are usually added to improve the thermal conductivity of silicone rubber. Studies have shown that when adding a single thermally conductive filler to prepare a high-conductivity composite material, a higher filling amount is usually required to form an effective thermal conductivity path in the matrix to improve the thermal conductivity. However, a high filling amount will inevitably cause a significant increase in the viscosity of the material, making it difficult to process, and the filler cannot be evenly dispersed in the matrix, so that the filler agglomerates in the matrix, resulting in high interfacial thermal resistance and discontinuous thermal paths; a high filling amount is not conducive to the mechanical properties of the composite material, and it is even more difficult to meet the needs of practical applications. Therefore, how to achieve the enhancement of the thermal conductivity of the composite material while maintaining its processing performance is still a huge challenge. Summary of the invention

[0004] In view of this, the object of the present invention is to provide a long-lasting antibacterial, thermally conductive, flame-retardant thermoplastic elastomer composite material based on TPC-ET and a preparation method thereof.

[0005] In order to achieve the above object, the present invention provides the following technical solutions:

[0006] One of the technical solutions of the present invention is a long-lasting antibacterial, heat-conductive, flame-retardant thermoplastic elastomer composite material based on TPC-ET, comprising the following raw materials in percentage by mass:

[0007] Thermoplastic polyester polyether elastomer copolymer: 30wt% to 80wt%;

[0008] Functional additives: 18.5wt% to 69.5wt%;

[0009] Processing aid: 0.5wt%~1.5wt%;

[0010] The functional additives are flame retardants, auxiliary flame retardants, thermal conductive fillers, compatibilizers, antibacterial agents and light stabilizers;

[0011] The flame retardant is an organic silicon flame retardant; the auxiliary flame retardant is a low-melting point glass powder; the thermal conductive filler is a nitride; and the antibacterial agent is polycyclotriphosphazene dihydroxydiphenyl sulfone microspheres loaded with nano silver particles.

[0012] The second technical solution of the present invention is a method for preparing the above-mentioned long-lasting antibacterial, heat-conductive, flame-retardant thermoplastic elastomer composite material based on TPC-ET, comprising the following steps:

[0013] The antibacterial agent, the light stabilizer and the processing aid are mixed evenly to obtain a mixture A; the flame retardant, the auxiliary flame retardant, the thermal conductive filler and the compatibilizer are mixed evenly to obtain a mixture B;

[0014] The thermoplastic polyester polyether elastomer copolymer, mixed material A and mixed material B are extruded and granulated to obtain the TPC-ET-based long-lasting antibacterial, heat-conductive and flame-retardant thermoplastic elastomer composite material.

[0015] The present invention discloses the following technical effects:

[0016] The present invention uses thermoplastic polyester polyether elastomer copolymer (TPC-ET) as a matrix material, utilizes the antibacterial and flame retardancy of polycyclotriphosphazene dihydroxydiphenyl sulfone microspheres loaded with nano-silver particles, uses polysiloxane as a flame retardant, low-melting point glass powder as an auxiliary combustion aid, and a compound of boron nitride and aluminum nitride as a thermal conductive filler to successfully prepare a TPC-ET elastomer composite material with long-lasting antibacterial, high thermal conductivity, flame retardancy and excellent mechanical properties. The TPC-ET elastomer composite material can be widely used in wires and cables, electronic appliances, medical treatment, transportation and other fields. DETAILED DESCRIPTION

[0017] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0018] It should be understood that the terms described in the present invention are only for describing a particular embodiment and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0019] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.

[0020] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to the skilled artisan. The present invention description and examples are exemplary only.

[0021] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.

[0022] One of the technical solutions of the present invention is a long-lasting antibacterial, heat-conductive, flame-retardant thermoplastic elastomer composite material based on TPC-ET, comprising the following raw materials in percentage by mass:

[0023] Thermoplastic polyester polyether elastomer copolymer (TPC-ET): 30wt% to 80wt%;

[0024] Functional additives: 18.5wt% to 69.5wt%;

[0025] Processing aid: 0.5wt%~1.5wt%;

[0026] The functional additives are flame retardants, auxiliary flame retardants, thermal conductive fillers, compatibilizers, antibacterial agents and light stabilizers;

[0027] The flame retardant is an organic silicon flame retardant; the auxiliary flame retardant is a low-melting point glass powder; the thermal conductive filler is a nitride; and the antibacterial agent is polycyclotriphosphazene dihydroxydiphenyl sulfone microspheres loaded with nano silver particles.

[0028] In some embodiments of the present invention, the flame retardant is polysiloxane; the melting point of the low-melting-point glass powder is in the range of 400-800° C., preferably 550-650° C.; and the nitride is hexagonal boron nitride and aluminum nitride.

[0029] The flame retardant mechanism of polysiloxane is mainly because it can promote the formation of carbon layer, improve the stability of carbon layer and improve the structure of carbon layer. When the material is burning, the flame retardant that begins to melt migrates to the surface of the substrate through the gap of the substrate, and forms a dense and stable silicon-containing coke carbon protective layer by compounding with the carbide of the elastomer. Compared with the conventional carbon layer, the carbon layer structure formed by the organosilicon flame retardant is more dense and stable, so it has better heat insulation effect, blocks the supply of oxygen, prevents the escape of volatiles from thermal degradation of polymers, and prevents the dripping of molten droplets. It has a strong inhibitory effect on many aspects of material combustion and has high flame retardant efficiency.

[0030] After the low-melting-point glass powder is heated and melted, it has high viscosity and will form vitrification. When preparing flame-retardant materials, low-melting-point glass powder with matching temperature is added in advance. After being thermally melted, part of the low-melting-point glass powder is heated and melted to seal with other materials to form a heat-insulating glass-like protective layer; the outer layer of low-melting-point glass powder is heated and melted to form an inorganic glass-like oxygen-isolating layer to protect the inner layer of resin from high-temperature oxidation; part of the low-melting-point glass powder reacts with the free radicals of the organic resin to form refractory substances; part of the low-melting-point glass powder will form an inorganic glass-like thermal conductive layer after cooling, which can conduct heat away at high speed; after the above reactions, the low-melting-point glass powder will eventually form a protective layer on the surface of the material.

[0031] The present invention introduces granular aluminum nitride and lamellar hexagonal boron nitride into TPC-ET for compounding, thereby achieving synergistic enhancement of the thermal conductivity of the TPC-ET thermoplastic elastomer composite material. With a small amount of thermally conductive filler added, the thermal conductivity path of the material is successfully improved without increasing the viscosity of the elastomer material, thereby obtaining a thermally conductive TPC-ET thermoplastic elastomer composite material with good processing performance, high thermal conductivity and excellent mechanical properties.

[0032] In some embodiments of the present invention, the method for preparing the polycyclotriphosphazene dihydroxydiphenyl sulfone microspheres loaded with nanosilver particles comprises the following steps:

[0033] After 4,4-dihydroxydiphenyl sulfone, hexachlorocyclotriphosphazene and acetonitrile are uniformly mixed, triethylamine is added for ultrasonic reaction, and after the ultrasonic reaction is completed, centrifugation, washing and drying are performed in sequence to obtain polycyclotriphosphazene dihydroxydiphenyl sulfone microspheres;

[0034] The polycyclotriphosphazene dihydroxydiphenyl sulfone microspheres are dispersed in an aqueous solution of ethylene glycol, and then a silver nitrate solution is added to carry out a heating and stirring reaction. After the heating and stirring reaction is completed, centrifugation, washing, and drying are performed in sequence to obtain the polycyclotriphosphazene dihydroxydiphenyl sulfone microspheres loaded with nanosilver particles.

[0035] Some transition metals can act as catalysts during the combustion process, catalyzing the carbonization of the matrix and accelerating the formation of a protective carbon layer. The carbon layer quickly covers the combustion surface of the material, isolating it from the outside air and blocking the heat transfer process. Among many transition metals, silver is a safe and non-toxic catalyst with high catalytic activity. It can effectively dissociate adsorbed oxygen and provide active sites for further oxidation of toxic gases such as carbon monoxide, thereby reducing the amount of toxic gas produced during the combustion process, effectively reducing the toxicity of smoke, and playing an important role in gas phase flame retardancy. During the combustion process, silver in the solid phase promotes cross-linking and captures active free radicals, thereby improving the thermal stability and flame retardancy of the material. However, silver has little flame retardant effect when used alone, or even no flame retardant effect, so silver needs to be used together with other flame retardants to play a flame retardant role. Phosphazene is a nitrogen-phosphorus multifunctional hybrid flame retardant. The molecular structure of hexachlorocyclotriphosphazene provides great possibilities for the preparation of multifunctional flame retardants due to its unique -P=N- structure and the diversity of side group structural units in the molecular skeleton, making it have great application prospects in different fields, such as flame-retardant polymer materials, battery electrolytes, medical materials and other fields.

[0036] The present invention firstly synthesizes polycyclotriphosphazene dihydroxyphenyl sulfone microspheres using hexachlorocyclotriphosphazene and dihydroxyphenyl sulfone, further uses polycyclotriphosphazene dihydroxyphenyl sulfone microspheres as carriers of silver (Ag) nanoparticles, uniformly loads Ag nanoparticles on the surface of polycyclotriphosphazene dihydroxyphenyl sulfone microspheres, and successfully prepares loaded nanosilver phosphazene microspheres with uniformly dispersed single substance Ag on the surface, and the loading rate of nanosilver particles is about 28%. Then, the loaded nanosilver phosphazene microspheres, polysiloxane and low-melting point glass powder are compounded and added into a thermoplastic polyester polyether elastomer copolymer TPC-ET flame retardant system to prepare a flame retardant TPC-ET thermoplastic elastomer composite material. During the combustion process, on the one hand, the loaded nano-silver phosphazene can induce the breaking of carbon-oxygen bonds and the coupling of free radicals in TPC-ET at a lower temperature, forming cross-linking points, promoting the cross-linking of TPC-ET, and thus improving its thermal stability; at the same time, the sulfuric acid, phosphoric acid, etc. produced by the decomposition of the loaded nano-silver phosphazene promote the small molecular substances produced by the degradation of TPC-ET to form a cross-linked carbon layer, which plays a barrier role and blocks the transfer of heat and substances; on the other hand, during the combustion process, the loaded nano-silver phosphazene promotes the melting of low-melting-point glass powder, increases its fluidity, enables it to be better filled between various materials, and synergizes with the polysiloxane flame retardant to make the formed carbon layer more tightly bonded to the substrate, thereby forming a denser barrier layer structure.

[0037] Antimicrobial agents are additives with bactericidal or antibacterial properties. Commonly used antimicrobial agents are organic antimicrobial agents, inorganic antimicrobial agents and natural antimicrobial agents. Because natural antimicrobial agents are restricted by various aspects such as production conditions and extraction technology, organic and inorganic antimicrobial agents still dominate the antimicrobial product series. Compared with organic antimicrobial agents, inorganic antimicrobial agents have the advantages of safety, non-volatility, durability and heat resistance. For the human body, inorganic antimicrobial agents are safer and milder than organic antimicrobial agents. Silver-based antimicrobial agents refer to antimicrobial agents with silver as the active ingredient. After silver enters the microorganism, it will react with the enzyme in the microorganism, inhibit the activity of the enzyme in the microorganism and prevent it from dividing and reproducing, thereby achieving an antibacterial effect. Silver-based antimicrobial agents have the advantages of broad-spectrum bactericidal properties, long-term bactericidal effects and high safety, and are widely used in rubber, plastics, textiles, coatings, biomedicine and other fields. However, silver-based antibacterial agents still have some defects, such as compatibility issues. Since silver is an inorganic metal material, it has poor compatibility with polymers. In particular, nano-sized silver antibacterial agents are prone to uneven dispersion and agglomeration when added to polymers, so that a large amount needs to be added to achieve the ideal antibacterial effect. At the same time, the mechanical properties of the antibacterial material are greatly reduced due to the presence of agglomerated silver particles and excessive addition. The loaded nano-silver phosphazene synthesized by the present invention solves the above problems well. The loaded nano-silver phosphazene is added to TPC-ET, has good compatibility, and has a long-lasting antibacterial effect. Moreover, the ideal antibacterial effect can be achieved with a very small amount of addition, and has almost no negative impact on the mechanical properties of TPC-ET, thereby obtaining a long-acting antibacterial TPC-ET elastomer material.

[0038] In some embodiments of the present invention, the molar ratio of 4,4-dihydroxydiphenyl sulfone to hexachlorocyclotriphosphazene is 3:1, and the molar concentration of 4,4-dihydroxydiphenyl sulfone in acetonitrile is 0.03 mol / L; the volume ratio of triethylamine to acetonitrile is 100:1.5; and the parameters of the ultrasonic reaction are set as follows: the ultrasonic power is 100 W, the reaction temperature is 45° C., and the reaction time is 5 h.

[0039] In some embodiments of the present invention, the aqueous solution of ethylene glycol is a mixed solution of ethylene glycol and water in a volume ratio of 1.5:1; the mass concentration of the polycyclotriphosphazene dihydroxydiphenyl sulfone microspheres in the aqueous solution of ethylene glycol is 2 g / L.

[0040] In some embodiments of the present invention, the parameters of the heating and stirring reaction are set as: 135° C. oil bath stirring reaction for 5 hours; the silver loading rate in the polycyclotriphosphazene dihydroxydiphenyl sulfone microspheres loaded with nanosilver particles is 25-30%.

[0041] In some embodiments of the present invention, the thermoplastic polyester polyether elastomer copolymer is a linear block copolymer of a polybutylene terephthalate hard segment and a polyether soft segment; the polyether soft segment is a non-crystalline polyether, and the non-crystalline polyether is a combination of one or more of polyethylene glycol ether, polypropylene glycol ether, and polybutylene glycol ether; the mass percentage of the polybutylene terephthalate hard segment and the polyether soft segment is 15 to 90:10 to 85.

[0042] The present invention utilizes a thermoplastic polyester polyether elastomer copolymer (TPC-ET) as a matrix material, wherein polyester is used as a hard segment in the copolymer and polyether is used as a soft segment in the copolymer, so that TPC-ET is a thermoplastic elastomer material having the properties of both plastic and rubber. By adjusting the ratio of polyester to polyether, the purpose of adjusting the elasticity and hardness of the material is achieved, and the hardness range can be selected from Shore 28D-80D.

[0043] In some embodiments of the present invention, the compatibilizer is a silane coupling agent; the light stabilizer is at least one of a hindered amine light stabilizer, a triazine ultraviolet absorber, a phenyltriazole ultraviolet absorber and a benzophenone ultraviolet absorber, and further, the light stabilizer is preferably poly [[6-[(1,1,3,3-tetramethylbutyl)amino]-s-triazine-2,4-diyl][(2,2,6,6-tetramethyl-4-piperidinyl)imino]]hexamethylene [(2,2,6,6-tetramethyl-4-piperidinyl)imino] (UV-944) light stabilizer.

[0044] In some embodiments of the present invention, the silane coupling agent is (3-aminopropyl)triethoxysilane coupling agent.

[0045] In some embodiments of the present invention, the processing aids are antioxidants and lubricants.

[0046] In some embodiments of the present invention, the antioxidant is selected from at least one of antioxidant 1098, antioxidant 1076, antioxidant S-9228, antioxidant 1010, antioxidant 168, antioxidant 1790 and antioxidant 412S;

[0047] The lubricant is selected from at least one of N,N'-ethylene bisstearamide, erucamide, oleamide, calcium stearate, ethylene bisoleamide and stearic acid.

[0048] The second technical solution of the present invention is a method for preparing the above-mentioned long-lasting antibacterial, heat-conductive, flame-retardant thermoplastic elastomer composite material based on TPC-ET, comprising the following steps:

[0049] The antibacterial agent, the light stabilizer and the processing aid are mixed evenly to obtain a mixture A; the flame retardant, the auxiliary flame retardant, the thermal conductive filler and the compatibilizer are mixed evenly to obtain a mixture B;

[0050] The thermoplastic polyester polyether elastomer copolymer, mixed material A and mixed material B are extruded and granulated to obtain the TPC-ET-based long-lasting antibacterial, heat-conductive and flame-retardant thermoplastic elastomer composite material.

[0051] In order to better understand the present invention, the content of the present invention is further explained below in conjunction with the embodiments, but the content of the present invention is not limited to the following embodiments.

[0052] Unless otherwise specified, the raw materials used in the examples are all commercially available products.

[0053] The preparation method of the polycyclotriphosphazene dihydroxydiphenyl sulfone microspheres loaded with nano-silver particles in the embodiment comprises the following steps:

[0054] Step 1. Weigh a certain mass of 4,4-dihydroxydiphenyl sulfone and hexachlorocyclotriphosphazene and place them in a reaction container, wherein the molar ratio of 4,4-dihydroxydiphenyl sulfone to hexachlorocyclotriphosphazene is 3:1; then add a certain amount of acetonitrile, wherein the molar concentration of 4,4-dihydroxydiphenyl sulfone in acetonitrile is 0.03 mol / L, and the molar concentration of hexachlorocyclotriphosphazene in acetonitrile is 0.01 mol / L, and then place the reactor in an ultrasonic wave for ultrasonic dispersion for 15 minutes to obtain a mixed solution; weigh a certain amount of triethylamine and add it to the above mixed solution, wherein the volume ratio of triethylamine to acetonitrile is 100:1.5. The mixed solution was placed in an ultrasonic bath for ultrasonic reaction, wherein the ultrasonic power was 100 W, the reaction temperature was 45° C., and the reaction time was 5 h. The mixed solution was then placed in a centrifuge at 10,000 rpm for 5 min. The product obtained by centrifugation was washed three times with acetonitrile and deionized water respectively. The product was dried in a vacuum oven at 65° C. for 5 h to obtain polycyclotriphosphazene dihydroxydiphenyl sulfone microspheres.

[0055] Step 2. Add a certain mass of polycyclotriphosphazene dihydroxydiphenyl sulfone microspheres into a reaction container, then add an aqueous solution of ethylene glycol (the volume ratio of ethylene glycol to water is 1.5:1), place under ultrasonic wave for ultrasonic dispersion for 30 minutes, and then stir for 15 minutes, wherein the mass concentration of polycyclotriphosphazene dihydroxydiphenyl sulfone microspheres in the aqueous solution of ethylene glycol is 2g / L, and obtain an aqueous solution of polycyclotriphosphazene dihydroxydiphenyl sulfone ethylene glycol; then take a certain amount of silver nitrate aqueous solution (0.1mmol / L) and add it to the above solution, stir for 15 minutes, and then put it into a 135°C oil bath pot, and react for 5 hours under stirring conditions; then place it in a centrifuge at 10000rpm for 5 minutes, wash the product obtained by centrifugation three times with deionized water, and finally dry it in a freeze drying box for 24 hours to obtain polycyclotriphosphazene dihydroxydiphenyl sulfone microspheres loaded with nano silver particles, and calculate the silver loading rate to be about 28% by the change in mass before and after loading.

[0056] Example 1

[0057] A long-lasting antibacterial, heat-conductive, flame-retardant thermoplastic elastomer composite material based on TPC-ET, the preparation method is as follows:

[0058] Step (1): Place TPC-ET (a linear block copolymer of polybutylene terephthalate hard segment and polybutylene glycol soft segment, with the mass percentage of hard segment to soft segment being 25:75) in a drying oven at 70° C. for 12 h.

[0059] Step (2): placing 5wt% of a nano-silver particle loaded polycyclotriphosphazene dihydroxydiphenyl sulfone microsphere antibacterial agent, 0.5wt% of poly[[6-[(1,1,3,3-tetramethylbutyl)amino]-s-triazine-2,4-diyl][(2,2,6,6-tetramethyl-4-piperidinyl)imino]]hexamethylene[(2,2,6,6-tetramethyl-4-piperidinyl)imino](UV-944) light stabilizer, 0.2wt% of an antioxidant 1010, 0.2wt% of an antioxidant 168, and 0.3wt% of a lubricant N,N'-ethylenebisstearamide in a high-speed mixer at room temperature and stirring for 10 minutes to obtain a mixture A, wherein the mass percentage of the mixture A to the total weight is 6.2wt%;

[0060] 11.25 wt% polysiloxane, 3.75 wt% low melting point glass powder, 8 wt% aluminum nitride, 8 wt% boron nitride and 0.35 wt% (3-aminopropyl) triethoxysilane coupling agent were placed in a high-speed mixer at 80°C and stirred for 10 min to obtain a mixture B, wherein the mass percentage of the mixture B in the total weight is 31.35 wt%.

[0061] Step (3): Place the dried TPC-ET obtained in step (1), the mixture A obtained in step (2), and the mixture B in three weight-loss feeders respectively, set the feeding parameters of the weight-loss feeders according to the mass percentage of TPC-ET: mixture A: mixture B = 62.45:6.2:31.35, and extrude, pull and pelletize through a co-rotating twin-screw extruder to obtain a long-lasting antibacterial, heat-conductive and flame-retardant thermoplastic elastomer composite material. Among them, TPC-ET and mixture A are added at the main feed port of the extruder, and mixture B is added at the side feed port of the extruder. The maximum setting temperature of the twin-screw extruder is 200°C, and the main screw speed is 300rad / min.

[0062] Example 2

[0063] A preparation method of a long-lasting antibacterial, thermally conductive, flame-retardant thermoplastic elastomer composite material based on TPC-ET, comprising the following steps:

[0064] Step (1): Place TPC-ET (a linear block copolymer of polybutylene terephthalate hard segment and polybutylene glycol soft segment, with the mass percentage of the hard segment to the soft segment being 30:70) in a drying oven at 80° C. for 12 h.

[0065] Step (2): 5 wt% of a nano-silver particle-loaded polycyclotriphosphazene dihydroxydiphenyl sulfone microsphere antibacterial agent, 0.5 wt% of a UV-944 light stabilizer, 0.2 wt% of an antioxidant 1010, 0.2 wt% of an antioxidant 168, and 0.3 wt% of a lubricant N,N'-ethylene bisstearamide are placed in a high-speed mixer at room temperature and stirred for 10 min to obtain a mixture A, wherein the mass percentage of the mixture A to the total weight is 6.2 wt%;

[0066] 9 wt % of polysiloxane, 4.5 wt % of low melting point glass powder, 8 wt % of aluminum nitride, 8 wt % of boron nitride and 0.35 wt % of (3-aminopropyl) triethoxysilane coupling agent were placed in a high-speed mixer at 80° C. and stirred for 10 min to obtain a mixture B, wherein the mass percentage of the mixture B in the total weight is 29.85 wt %.

[0067] Step (3): Place the dried TPC-ET obtained in step (1), the mixture A obtained in step (2), and the mixture B in three weight-loss feeders respectively, set the feeding parameters of the weight-loss feeders according to the mass percentage of TPC-ET: mixture A: mixture B = 63.95:6.2:29.85, and extrude, pull and pelletize through a co-rotating twin-screw extruder to obtain a long-lasting antibacterial, heat-conductive and flame-retardant thermoplastic elastomer composite material. Among them, TPC-ET and mixture A are added at the main feed port of the extruder, and mixture B is added at the side feed port of the extruder. The maximum setting temperature of the twin-screw extruder is 210°C, and the main screw speed is 300rad / min.

[0068] Example 3

[0069] A preparation method of a long-lasting antibacterial, thermally conductive, flame-retardant thermoplastic elastomer composite material based on TPC-ET, comprising the following steps:

[0070] Step (1): Place TPC-ET (a linear block copolymer of polybutylene terephthalate hard segment and polybutylene glycol soft segment, with the mass percentage of the hard segment and the soft segment being 50:50) in a drying oven at 80° C. for 12 h.

[0071] Step (2): 5 wt% of a nano-silver particle-loaded polycyclotriphosphazene dihydroxydiphenyl sulfone microsphere antibacterial agent, 0.5 wt% of a UV-944 light stabilizer, 0.2 wt% of an antioxidant 1010, 0.2 wt% of an antioxidant 168, and 0.3 wt% of a lubricant N,N'-ethylene bisstearamide are placed in a high-speed mixer at room temperature and stirred for 10 min to obtain a mixture A, wherein the mass percentage of the mixture A to the total weight is 6.2 wt%;

[0072] 8 wt % of polysiloxane, 4 wt % of low melting point glass powder, 8 wt % of aluminum nitride, 8 wt % of boron nitride and 0.35 wt % of (3-aminopropyl) triethoxysilane coupling agent were placed in a high-speed mixer at 80° C. and stirred for 10 min to obtain a mixture B, wherein the mass percentage of the mixture B in the total weight is 28.35 wt %.

[0073] Step (3): Place the dried TPC-ET obtained in step (1), the mixture A obtained in step (2), and the mixture B in three weight-loss feeders respectively, set the feeding parameters of the weight-loss feeders according to the mass percentage of TPC-ET: mixture A: mixture B = 65.45:6.2:28.35, and extrude, pull and pelletize through a co-rotating twin-screw extruder to obtain a long-lasting antibacterial, heat-conductive and flame-retardant thermoplastic elastomer composite material. Among them, TPC-ET and mixture A are added at the main feed port of the extruder, and mixture B is added at the side feed port of the extruder. The maximum setting temperature of the twin-screw extruder is 230°C, and the main screw speed is 300rad / min.

[0074] Example 4

[0075] A preparation method of a long-lasting antibacterial, thermally conductive, flame-retardant thermoplastic elastomer composite material based on TPC-ET, comprising the following steps:

[0076] Step (1): Place TPC-ET (a linear block copolymer of polybutylene terephthalate hard segment and polybutylene glycol soft segment, with the mass percentage of hard segment to soft segment being 56:44) in a drying oven at 80° C. for 12 h.

[0077] Step (2): 5 wt% of a nano-silver particle-loaded polycyclotriphosphazene dihydroxydiphenyl sulfone microsphere antibacterial agent, 0.5 wt% of a UV-944 light stabilizer, 0.2 wt% of an antioxidant 1010, 0.2 wt% of an antioxidant 168, and 0.3 wt% of a lubricant N,N'-ethylene bisstearamide are placed in a high-speed mixer at room temperature and stirred for 10 min to obtain a mixture A, wherein the mass percentage of the mixture A to the total weight is 6.2 wt%;

[0078] 7 wt % of polysiloxane, 3.5 wt % of low melting point glass powder, 8 wt % of aluminum nitride, 8 wt % of boron nitride and 0.35 wt % of (3-aminopropyl) triethoxysilane coupling agent were placed in a high-speed mixer at 80° C. and stirred for 10 min to obtain a mixture B, wherein the mass percentage of the mixture B in the total weight is 26.85 wt %.

[0079] Step (3): Place the dried TPC-ET obtained in step (1), the mixture A obtained in step (2), and the mixture B in three weight-loss feeders respectively, set the feeding parameters of the weight-loss feeders according to the mass percentage of TPC-ET: mixture A: mixture B = 66.95:6.2:26.85, and extrude, pull and pelletize through a co-rotating twin-screw extruder to obtain a long-lasting antibacterial, heat-conductive and flame-retardant thermoplastic elastomer composite material. Among them, TPC-ET and mixture A are added at the main feed port of the extruder, and mixture B is added at the side feed port of the extruder. The maximum setting temperature of the twin-screw extruder is 250°C, and the main screw speed is 300rad / min.

[0080] Comparative Example 1

[0081] Step (1): Place TPC-ET (a linear block copolymer of polybutylene terephthalate hard segment and polybutylene glycol soft segment, with the mass percentage of hard segment to soft segment being 25:75) in a drying oven at 70° C. for 12 h.

[0082] Step (2): placing 0.5 wt% UV-944 light stabilizer, 0.2 wt% antioxidant 1010, 0.2 wt% antioxidant 168, and 0.3 wt% lubricant N,N'-ethylene bisstearamide in a high-speed mixer at room temperature and stirring for 10 min to obtain a mixture A, wherein the mass percentage of the mixture A to the total weight is 1.2 wt%;

[0083] 11.25 wt% polysiloxane, 3.75 wt% low melting point glass powder, 8 wt% aluminum nitride, 8 wt% boron nitride and 0.35 wt% (3-aminopropyl) triethoxysilane coupling agent were placed in a high-speed mixer at 80°C and stirred for 10 min to obtain a mixture B, wherein the mass percentage of the mixture B in the total weight is 31.35 wt%.

[0084] Step (3): The dried TPC-ET obtained in step (1), the mixture A obtained in step (2), and the mixture B are placed in three weight-loss feeders respectively, and the feeding parameters of the weight-loss feeder are set according to the mass percentage of TPC-ET: mixture A: mixture B = 67.45:1.2:31.35, and the long-lasting antibacterial, heat-conductive, flame-retardant thermoplastic elastomer composite material is obtained by extrusion, pulling and pelletizing through a co-rotating twin-screw extruder. Among them, TPC-ET and mixture A are added at the main feed port of the extruder, and mixture B is added at the side feed port of the extruder. The maximum setting temperature of the twin-screw extruder is 200°C, and the main screw speed is 300rad / min. (That is, the difference from Example 1 is that the polycyclotriphosphazene dihydroxydiphenyl sulfone microspheres loaded with nano-silver particles are not added).

[0085] Comparative Example 2

[0086] Step (1): Place TPC-ET (a linear block copolymer of polybutylene terephthalate hard segment and polybutylene glycol soft segment, with the mass percentage of hard segment to soft segment being 25:75) in a drying oven at 70° C. for 12 h.

[0087] Step (2): placing 5 wt% of nano silver antibacterial agent, 0.5 wt% of UV-944 light stabilizer, 0.2 wt% of antioxidant 1010, 0.2 wt% of antioxidant 168, and 0.3 wt% of lubricant N,N'-ethylene bisstearamide in a high-speed mixer at room temperature and stirring for 10 min to obtain a mixture A, wherein the mass percentage of the mixture A to the total weight is 6.2 wt%;

[0088] 11.25 wt% polysiloxane, 3.75 wt% low melting point glass powder, 8 wt% aluminum nitride, 8 wt% boron nitride and 0.35 wt% (3-aminopropyl) triethoxysilane coupling agent were placed in a high-speed mixer at 80°C and stirred for 10 min to obtain a mixture B, wherein the mass percentage of the mixture B in the total weight is 31.35 wt%.

[0089] Step (3): The dried TPC-ET obtained in step (1), the mixture A obtained in step (2), and the mixture B are placed in three weightless feeders respectively, and the feeding parameters of the weightless feeder are set according to the mass percentage of TPC-ET: mixture A: mixture B = 67.45:1.2:31.35, and the long-lasting antibacterial, heat-conductive, flame-retardant thermoplastic elastomer composite material is obtained by extrusion, pulling and pelletizing through a co-rotating twin-screw extruder. Among them, TPC-ET and mixture A are added at the main feed port of the extruder, and mixture B is added at the side feed port of the extruder. The maximum setting temperature of the twin-screw extruder is 200°C, and the main screw speed is 300rad / min. (That is, the difference from Example 1 is that the loaded nano-silver particles polycyclotriphosphazene dihydroxydiphenyl sulfone microspheres are replaced with nano-Ag).

[0090] Comparative Example 3

[0091] Step (1): Place TPC-ET (a linear block copolymer of polybutylene terephthalate hard segment and polybutylene glycol soft segment, with the mass percentage of hard segment to soft segment being 25:75) in a drying oven at 70° C. for 12 h.

[0092] Step (2): 5 wt% of a nano-silver particle-loaded polycyclotriphosphazene dihydroxydiphenyl sulfone microsphere antibacterial agent, 0.5 wt% of a UV-944 light stabilizer, 0.2 wt% of an antioxidant 1010, 0.2 wt% of an antioxidant 168, and 0.3 wt% of a lubricant N,N'-ethylene bisstearamide are placed in a high-speed mixer at room temperature and stirred for 10 min to obtain a mixture A, wherein the mass percentage of the mixture A to the total weight is 6.2 wt%;

[0093] 15 wt% polysiloxane, 8 wt% aluminum nitride, 8 wt% boron nitride and 0.35 wt% (3-aminopropyl) triethoxysilane coupling agent were placed in a high-speed mixer at 80°C and stirred for 10 min to obtain a mixture B, wherein the mass percentage of the mixture B in the total weight is 31.35 wt%.

[0094] Step (3): Place the dried TPC-ET obtained in step (1), mixture A and mixture B obtained in step (2) in three weight-loss feeders respectively, set the feeding parameters of the weight-loss feeder according to the mass percentage of TPC-ET: mixture A: mixture B = 62.45:6.2:31.35, and extrude, pull and pelletize through a co-rotating twin-screw extruder to obtain a long-lasting antibacterial, heat-conductive and flame-retardant thermoplastic elastomer composite material. Among them, TPC-ET and mixture A are added at the main feed port of the extruder, and mixture B is added at the side feed port of the extruder. The maximum setting temperature of the twin-screw extruder is 200°C, and the main screw speed is 300rad / min. (That is, the difference from Example 1 is that low-melting point glass powder is not added).

[0095] Comparative Example 4

[0096] Step (1): Place TPC-ET (a linear block copolymer of polybutylene terephthalate hard segment and polybutylene glycol soft segment, with the mass percentage of hard segment to soft segment being 25:75) in a drying oven at 70° C. for 12 h.

[0097] Step (2): 5 wt% of a nano-silver particle-loaded polycyclotriphosphazene dihydroxydiphenyl sulfone microsphere antibacterial agent, 0.5 wt% of a UV-944 light stabilizer, 0.2 wt% of an antioxidant 1010, 0.2 wt% of an antioxidant 168, and 0.3 wt% of a lubricant N,N'-ethylene bisstearamide are placed in a high-speed mixer at room temperature and stirred for 10 min to obtain a mixture A, wherein the mass percentage of the mixture A to the total weight is 6.2 wt%;

[0098] 15 wt% of low melting point glass powder, 8 wt% of aluminum nitride, 8 wt% of boron nitride and 0.35 wt% of (3-aminopropyl) triethoxysilane coupling agent were placed in a high-speed mixer at 80°C and stirred for 10 min to obtain a mixture B, wherein the mass percentage of the mixture B in the total weight is 31.35 wt%.

[0099] Step (3): Place the dried TPC-ET obtained in step (1), mixture A and mixture B obtained in step (2) in three weight-loss feeders respectively, set the feeding parameters of the weight-loss feeder according to the mass percentage of TPC-ET: mixture A: mixture B = 62.45:6.2:31.35, and extrude, pull and pelletize through a co-rotating twin-screw extruder to obtain a long-lasting antibacterial, heat-conductive and flame-retardant thermoplastic elastomer composite material. Among them, TPC-ET and mixture A are added at the main feed port of the extruder, and mixture B is added at the side feed port of the extruder. The maximum setting temperature of the twin-screw extruder is 200°C, and the main screw speed is 300rad / min. (That is, the difference from Example 1 is that polysiloxane is not added).

[0100] Comparative Example 5

[0101] Step (1): Place TPC-ET (a linear block copolymer of polybutylene terephthalate hard segment and polybutylene glycol soft segment, with the mass percentage of hard segment to soft segment being 25:75) in a drying oven at 70° C. for 12 h.

[0102] Step (2): placing 5wt% of a nano-silver particle loaded polycyclotriphosphazene dihydroxydiphenyl sulfone microsphere antibacterial agent, 0.5wt% of poly[[6-[(1,1,3,3-tetramethylbutyl)amino]-s-triazine-2,4-diyl][(2,2,6,6-tetramethyl-4-piperidinyl)imino]]hexamethylene[(2,2,6,6-tetramethyl-4-piperidinyl)imino](UV-944) light stabilizer, 0.2wt% of an antioxidant 1010, 0.2wt% of an antioxidant 168, and 0.3wt% of a lubricant N,N'-ethylenebisstearamide in a high-speed mixer at room temperature and stirring for 10 minutes to obtain a mixture A, wherein the mass percentage of the mixture A to the total weight is 6.2wt%;

[0103] 11.25 wt% of intumescent flame retardant ammonium polyphosphate, 3.75 wt% of auxiliary flame retardant pentaerythritol, 8 wt% of aluminum nitride, 8 wt% of boron nitride and 0.35 wt% of (3-aminopropyl) triethoxysilane coupling agent were placed in a high-speed mixer at 80° C. and stirred for 10 min to obtain a mixture B, wherein the mass percentage of the mixture B in the total weight is 31.35 wt%.

[0104] Step (3): Place the dried TPC-ET obtained in step (1), the mixture A obtained in step (2), and the mixture B in three weight-loss feeders respectively, set the feeding parameters of the weight-loss feeders according to the mass percentage of TPC-ET: mixture A: mixture B = 62.45:6.2:31.35, and extrude, pull and pelletize through a co-rotating twin-screw extruder to obtain a long-lasting antibacterial, heat-conductive and flame-retardant thermoplastic elastomer composite material. Among them, TPC-ET and mixture A are added at the main feed port of the extruder, and mixture B is added at the side feed port of the extruder. The maximum setting temperature of the twin-screw extruder is 200°C, and the main screw speed is 300rad / min.

[0105] Comparative Example 6

[0106] Step (1): Place TPC-ET (a linear block copolymer of polybutylene terephthalate hard segment and polybutylene glycol soft segment, with the mass percentage of hard segment to soft segment being 25:75) in a drying oven at 70° C. for 12 h.

[0107] Step (2): placing 5wt% of a nano-silver particle loaded polycyclotriphosphazene dihydroxydiphenyl sulfone microsphere antibacterial agent, 0.5wt% of poly[[6-[(1,1,3,3-tetramethylbutyl)amino]-s-triazine-2,4-diyl][(2,2,6,6-tetramethyl-4-piperidinyl)imino]]hexamethylene[(2,2,6,6-tetramethyl-4-piperidinyl)imino](UV-944) light stabilizer, 0.2wt% of an antioxidant 1010, 0.2wt% of an antioxidant 168, and 0.3wt% of a lubricant N,N'-ethylenebisstearamide in a high-speed mixer at room temperature and stirring for 10 minutes to obtain a mixture A, wherein the mass percentage of the mixture A to the total weight is 6.2wt%;

[0108] 11.25 wt% of metal hydroxide flame retardant magnesium hydroxide, 3.75 wt% of auxiliary flame retardant low-melting point glass powder, 8 wt% of aluminum nitride, 8 wt% of boron nitride and 0.35 wt% of (3-aminopropyl) triethoxysilane coupling agent are placed in a high-speed mixer at 80° C. and stirred for 10 min to obtain a mixture B, wherein the mass percentage of the mixture B in the total weight is 31.35 wt%.

[0109] Step (3): Place the dried TPC-ET obtained in step (1), the mixture A obtained in step (2), and the mixture B in three weight-loss feeders respectively, set the feeding parameters of the weight-loss feeders according to the mass percentage of TPC-ET: mixture A: mixture B = 62.45:6.2:31.35, and extrude, pull and pelletize through a co-rotating twin-screw extruder to obtain a long-lasting antibacterial, heat-conductive and flame-retardant thermoplastic elastomer composite material. Among them, TPC-ET and mixture A are added at the main feed port of the extruder, and mixture B is added at the side feed port of the extruder. The maximum setting temperature of the twin-screw extruder is 200°C, and the main screw speed is 300rad / min.

[0110] Comparative Example 7

[0111] Step (1): Place TPC-ET (a linear block copolymer of polybutylene terephthalate hard segment and polybutylene glycol soft segment, with the mass percentage of hard segment to soft segment being 25:75) in a drying oven at 70° C. for 12 h.

[0112] Step (2): placing 5wt% of a nano-silver particle loaded polycyclotriphosphazene dihydroxydiphenyl sulfone microsphere antibacterial agent, 0.5wt% of poly[[6-[(1,1,3,3-tetramethylbutyl)amino]-s-triazine-2,4-diyl][(2,2,6,6-tetramethyl-4-piperidinyl)imino]]hexamethylene[(2,2,6,6-tetramethyl-4-piperidinyl)imino](UV-944) light stabilizer, 0.2wt% of an antioxidant 1010, 0.2wt% of an antioxidant 168, and 0.3wt% of a lubricant N,N'-ethylenebisstearamide in a high-speed mixer at room temperature and stirring for 10 minutes to obtain a mixture A, wherein the mass percentage of the mixture A to the total weight is 6.2wt%;

[0113] 11.25 wt% of brominated flame retardant decabromodiphenylethane, 3.75 wt% of auxiliary flame retardant antimony trioxide, 8 wt% of aluminum nitride, 8 wt% of boron nitride and 0.35 wt% of (3-aminopropyl) triethoxysilane coupling agent were placed in a high-speed mixer at 80° C. and stirred for 10 min to obtain a mixture B, wherein the mass percentage of the mixture B in the total weight is 31.35 wt%.

[0114] Step (3): Place the dried TPC-ET obtained in step (1), the mixture A obtained in step (2), and the mixture B in three weight-loss feeders respectively, set the feeding parameters of the weight-loss feeders according to the mass percentage of TPC-ET: mixture A: mixture B = 62.45:6.2:31.35, and extrude, pull and pelletize through a co-rotating twin-screw extruder to obtain a long-lasting antibacterial, heat-conductive and flame-retardant thermoplastic elastomer composite material. Among them, TPC-ET and mixture A are added at the main feed port of the extruder, and mixture B is added at the side feed port of the extruder. The maximum setting temperature of the twin-screw extruder is 200°C, and the main screw speed is 300rad / min.

[0115] Comparative Example 8

[0116] Step (1): Place TPC-ET (a linear block copolymer of polybutylene terephthalate hard segment and polybutylene glycol soft segment, with the mass percentage of hard segment to soft segment being 25:75) in a drying oven at 70° C. for 12 h.

[0117] Step (2): 5 wt% of a nano-silver particle-loaded polycyclotriphosphazene dihydroxydiphenyl sulfone microsphere antibacterial agent, 0.5 wt% of a UV-944 light stabilizer, 0.2 wt% of an antioxidant 1010, 0.2 wt% of an antioxidant 168, and 0.3 wt% of a lubricant N,N'-ethylene bisstearamide are placed in a high-speed mixer at room temperature and stirred for 10 min to obtain a mixture A, wherein the mass percentage of the mixture A to the total weight is 6.2 wt%;

[0118] 11.25 wt% polysiloxane, 3.75 wt% low melting point glass powder, 16 wt% aluminum nitride and 0.35 wt% (3-aminopropyl) triethoxysilane coupling agent were placed in a high-speed mixer at 80°C and stirred for 10 min to obtain a mixture B, wherein the mass percentage of the mixture B in the total weight is 31.35 wt%.

[0119] Step (3): Place the dried TPC-ET obtained in step (1), mixture A and mixture B obtained in step (2) in three weight-loss feeders respectively, set the feeding parameters of the weight-loss feeder according to the mass percentage of TPC-ET: mixture A: mixture B = 62.45:6.2:31.35, and extrude, pull and pelletize through a co-rotating twin-screw extruder to obtain a long-lasting antibacterial, heat-conductive and flame-retardant thermoplastic elastomer composite material. Among them, TPC-ET and mixture A are added at the main feed port of the extruder, and mixture B is added at the side feed port of the extruder. The maximum setting temperature of the twin-screw extruder is 200°C, and the main screw speed is 300rad / min. (That is, the difference from Example 1 is that only one thermally conductive filler, aluminum nitride, is added).

[0120] Comparative Example 9

[0121] Step (1): Place TPC-ET (a linear block copolymer of polybutylene terephthalate hard segment and polybutylene glycol soft segment, with the mass percentage of hard segment to soft segment being 25:75) in a drying oven at 70° C. for 12 h.

[0122] Step (2): 5 wt% of a nano-silver particle-loaded polycyclotriphosphazene dihydroxydiphenyl sulfone microsphere antibacterial agent, 0.5 wt% of a UV-944 light stabilizer, 0.2 wt% of an antioxidant 1010, 0.2 wt% of an antioxidant 168, and 0.3 wt% of a lubricant N,N'-ethylene bisstearamide are placed in a high-speed mixer at room temperature and stirred for 10 min to obtain a mixture A, wherein the mass percentage of the mixture A to the total weight is 6.2 wt%;

[0123] 11.25 wt% polysiloxane, 3.75 wt% low melting point glass powder, 16 wt% boron nitride and 0.35 wt% (3-aminopropyl) triethoxysilane coupling agent were placed in a high-speed mixer at 80°C and stirred for 10 min to obtain a mixture B, wherein the mass percentage of the mixture B in the total weight is 31.35 wt%.

[0124] Step (3): The dried TPC-ET obtained in step (1), the mixture A obtained in step (2), and the mixture B are placed in three weight-loss feeders respectively, and the feeding parameters of the weight-loss feeders are set according to the mass percentage of TPC-ET: mixture A: mixture B = 62.45:6.2:31.35. The mixture is extruded, stretched and pelletized by a co-rotating twin-screw extruder to obtain a long-lasting antibacterial, heat-conductive and flame-retardant thermoplastic elastomer composite material. Among them, TPC-ET and mixture A are added at the main feeding port of the extruder, and mixture B is added at the side feeding port of the extruder. The maximum setting temperature of the twin-screw extruder is 200°C, and the main screw speed is 300rad / min. (That is, the difference from Example 1 is that only one thermal conductive filler, boron nitride, is added)

[0125] The performance test results of the thermoplastic elastomer materials obtained in the examples and comparative examples are shown in Table 1 and Table 2.

[0126] Table 1 Mechanical properties and antibacterial test results of examples and comparative examples

[0127]

[0128] Table 2 Flame retardant performance test and performance test results of examples and comparative examples

[0129]

[0130] The following conclusions can be drawn from the data in Tables 1 and 2:

[0131] Compared with Example 1 and Comparative Example 1, Comparative Example 1 does not add the antibacterial agent of polycyclotriphosphazene dihydroxydiphenyl sulfone microspheres loaded with nanosilver particles, so the result is that the obtained elastomeric material has no antibacterial properties, and UL-94 is V-1, and the flame retardant property is worse than that of Example 1 (V-0). The results of cone calorimeter test also show that the flame retardant property of Example 1 is better than that of Comparative Example 1. Similarly, compared with Example 1 and Comparative Example 2, the antibacterial agent used in Comparative Example 2 is nanosilver, which is an inorganic antibacterial agent. It is directly added to the elastomer and has poor compatibility with the elastomer. Nanosilver is easy to agglomerate, resulting in the elastomeric material obtained in Comparative Example 2 not only having poor antibacterial effect, but also having much lower mechanical properties than Example 1, and the flame retardant is not ideal. The reason for the difference in the test results of Example 1, Comparative Example 1 and Comparative Example 2 is that, during the combustion process, although silver can effectively dissociate the adsorbed oxygen, it provides active sites for further oxidation of toxic gases such as carbon monoxide, thereby reducing the amount of toxic gas produced during the combustion process, effectively reducing the toxicity of smoke, and playing an important role in gas phase flame retardancy, which is confirmed by the data of carbon monoxide yield measured by cone calorimeters in Example 1 and Comparative Examples 1 and 2. During the combustion process, silver in the solid phase promotes crosslinking and captures active free radicals, thereby improving the thermal stability and flame retardancy of the material. However, silver has little flame retardant effect when used alone, and even has no flame retardant effect, so it is necessary to use silver together with other flame retardants to play a flame retardant effect. Phosphazene is a nitrogen-phosphorus multifunctional hybrid flame retardant, in which the molecular structure of hexachlorocyclotriphosphazene provides great possibilities for the preparation of multifunctional flame retardants due to the presence of its unique -P=N- structure and the diversity of side group structural units in the molecular skeleton. The nano-silver particle-loaded polycyclotriphosphazene dihydroxydiphenyl sulfone microsphere antibacterial agent used in the present invention not only has an antibacterial effect, but also has a flame retardant effect. On the one hand, the polycyclotriphosphazene dihydroxydiphenyl sulfone itself has flame retardancy. In addition, during the combustion process, the loaded nano-silver phosphazene can induce the rupture of the carbon-oxygen bond in TPC-ET and the coupling of free radicals at a lower temperature to form cross-linking points, promote the cross-linking of TPC-ET, and thus improve its thermal stability; at the same time, sulfuric acid, phosphoric acid, etc. generated by the decomposition of the loaded nano-silver phosphazene promote the small molecular substances generated by the degradation of TPC-ET to form a cross-linked carbon layer, which plays a barrier role and blocks the transfer of heat and substances; in addition, during the combustion process, the loaded nano-silver phosphazene promotes the melting of the low-melting point glass powder to increase its fluidity, so that it can be better filled between various materials, and synergistically acts with the polysiloxane flame retardant to make the formed carbon layer more closely combined with the substrate, thereby forming a more compact barrier layer structure.

[0132] Compared with Example 1 and Comparative Example 3, in Comparative Example 3, only polysiloxane flame retardant was added without low melting point glass powder, and its flame retardant performance only reached V-2 level, and the cone calorimeter test data showed that the flame retardant performance of the system without polysiloxane flame retardant was very poor. Compared with Example 1 and Comparative Example 4, in Comparative Example 4, only low melting point glass powder was added without polysiloxane flame retardant, and its flame retardant performance was V-1 level. The cone calorimeter test results also showed that the flame retardancy of Comparative Example 4 was not ideal due to the lack of low melting point glass powder. This is because the present invention utilizes low-melting-point glass powder as an auxiliary flame retardant. After the low-melting-point glass powder is heated and melted, it has high viscosity and will form vitrification. The low-melting-point glass powder inside some materials is heated and melted and sealed with other materials to form a heat-insulating glass-state protective layer. The outer layer of low-melting-point glass powder is heated and melted to form an inorganic glass-like oxygen-isolating layer to protect the inner layer of resin from high-temperature oxidation. Some low-melting-point glass powder reacts with free radicals of organic resin to form refractory substances. Some low-melting-point glass powder will form an inorganic glass-like thermal conductive layer after cooling down, which can conduct heat away at high speed. After the above reaction, the low-melting-point glass powder will eventually prevent further combustion of the system.

[0133] Example 1, Comparative Example 5 and Comparative Example 6 are compared. Comparative Example 5 adds an intumescent flame retardant system, and Comparative Example 6 adds a metal hydroxide flame retardant system. The same amount of flame retardant and auxiliary flame retardant as in Example 1 is added, and its flame retardant performance only reaches V-1 level and HB, and the cone calorimeter test data is also worse than the test data of the synergistic flame retardant of adding polysiloxane and low-melting glass powder in Example 1, and the mechanical properties in Comparative Example 5 and Comparative Example 6 are worse than those in Example 1, especially the mechanical properties of Comparative Example 6 with the addition of magnesium hydroxide flame retardant are the worst among the three. In summary, the intumescent flame retardant system in Comparative Example 5 and the metal hydroxide flame retardant system in Comparative Example 6 are not as good as the flame retardant effect of the polysiloxane flame retardant and low-melting glass powder used in the present invention. Comparative Example 6 also shows that magnesium hydroxide and low-melting glass powder have no flame retardant synergistic effect.

[0134] Example 1 is compared with Comparative Example 7. Comparative Example 7 adds a brominated flame retardant system. The results are very good in terms of mechanical and flame retardant test data, but brominated flame retardants are halogen flame retardants, which are considered to be environmentally unfriendly flame retardants in most European and American countries. Although there is still controversy over the amount and nature of toxic substances produced by brominated flame retardants during combustion, for example, polymers without flame retardants are more likely to burn and also release harmful substances, the impact of organic brominated flame retardants on human health is still undeniable, so they have become the subject of restricted use. Therefore, although the flame retardant effect is very good and the mechanical properties are also good, brominated flame retardants are not recommended.

[0135] Compared with Example 1, Comparative Example 8 and Comparative Example 9, the thermally conductive filler used in Example 1 is boron nitride and aluminum nitride compounded in a mass percentage of 1:1, while Comparative Example 8 only adds one thermally conductive filler, aluminum nitride, and Comparative Example 9 only adds one thermally conductive filler, boron nitride. Although the total amount of thermally conductive fillers added to the three systems is 16%, the thermal conductivity test data in Table 1 show that Example 1 has the highest thermal conductivity and the best thermal conductivity. This is because granular aluminum nitride and lamellar hexagonal boron nitride are compounded to achieve synergistic enhancement of the thermal conductivity of the TPC-ET thermoplastic elastomer composite material. When the amount of thermally conductive filler added is small, the thermal conductivity path of the material is successfully improved without increasing the viscosity of the elastomer material, and a thermally conductive TPC-ET thermoplastic elastomer composite material with good processing performance, high thermal conductivity and excellent mechanical properties is obtained, while a single-shaped thermally conductive filler is difficult to achieve such an effect when the addition amount is the same.

[0136] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A long-lasting antibacterial, thermally conductive, flame-retardant thermoplastic elastomer composite material based on TPC-ET, characterized in that: The preparation steps are as follows: Step (1): placing the linear block copolymer of polybutylene terephthalate hard segment and polybutylene glycol soft segment in a drying oven at 70° C. for 12 hours; the mass percentage of the hard segment to the soft segment in the linear block copolymer of polybutylene terephthalate hard segment and polybutylene glycol soft segment is 25:75; Step (2): 5 wt% of a nano-silver particle-loaded polycyclotriphosphazene dihydroxydiphenyl sulfone microsphere antibacterial agent, 0.5 wt% of poly[[6-[(1,1,3,3-tetramethylbutyl)amino]-s-triazine-2,4-diyl][(2,2,6,6-tetramethyl-4-piperidinyl)imino]]hexamethylene[(2,2,6,6-tetramethyl-4-piperidinyl)imino] light stabilizer, 0.2 wt% of an antioxidant 1010, 0.2 wt% of an antioxidant 168, and 0.3 wt% of a lubricant N,N'-ethylenebisstearamide are placed in a high-speed mixer at room temperature and stirred for 10 min to obtain a mixture A, wherein the mass percentage of the mixture A to the total weight is 6.2 wt%; 11.25 wt% polysiloxane, 3.75 wt% low melting point glass powder, 8 wt% aluminum nitride, 8 wt% boron nitride and 0.35 wt% (3-aminopropyl) triethoxysilane coupling agent were placed in a high-speed mixer at 80° C. and stirred for 10 min to obtain a mixture B, wherein the mass percentage of the mixture B in the total weight is 31.35 wt%; Step (3): placing the dried linear block copolymer of polybutylene terephthalate hard segment and polybutylene glycol soft segment obtained in step (1), mixed material A and mixed material B obtained in step (2) in three weightlessness feeders respectively, setting the feeding parameters of the weightlessness feeders according to the mass percentage of the linear block copolymer of polybutylene terephthalate hard segment and polybutylene glycol soft segment: mixed material A: mixed material B = 62.45:6.2:31.35, and obtaining a long-lasting antibacterial, heat-conductive, flame-retardant thermoplastic elastomer composite material by extruding, pulling and pelletizing through a co-rotating twin-screw extruder; wherein the linear block copolymer of polybutylene terephthalate hard segment and polybutylene glycol soft segment and mixed material A are added at the main feeding port of the extruder, and mixed material B is added at the side feeding port of the extruder, the maximum setting temperature of the twin-screw extruder is 200° C., and the main screw speed is 300 rad / min; The preparation method of the polycyclotriphosphazene dihydroxydiphenyl sulfone microspheres loaded with nano-silver particles comprises the following steps: Step 1. Weigh a certain mass of 4,4-dihydroxydiphenyl sulfone and hexachlorocyclotriphosphazene and place them in a reaction container, wherein the molar ratio of 4,4-dihydroxydiphenyl sulfone to hexachlorocyclotriphosphazene is 3:1; then add a certain amount of acetonitrile, wherein the molar concentration of 4,4-dihydroxydiphenyl sulfone in acetonitrile is 0.03 mol / L, and the molar concentration of hexachlorocyclotriphosphazene in acetonitrile is 0.01 mol / L, and then place the reactor in an ultrasonic wave for ultrasonic dispersion for 15 minutes to obtain a mixed solution; weigh a certain mass of 4,4-dihydroxydiphenyl sulfone and hexachlorocyclotriphosphazene, wherein the molar ratio of 4,4-dihydroxydiphenyl sulfone to hexachlorocyclotriphosphazene is 3:1; then add a certain amount of acetonitrile, wherein the molar concentration of 4,4-dihydroxydiphenyl sulfone in acetonitrile is 0.03 mol / L, and the molar concentration of hexachlorocyclotriphosphazene in acetonitrile is 0.01 mol / L, and then place the reactor in an ultrasonic wave for ultrasonic dispersion for 15 minutes to obtain a mixed solution; A quantitative amount of triethylamine is added to the mixed solution, wherein the volume ratio of triethylamine to acetonitrile is 100:1.5; the mixed solution is placed in an ultrasonic wave for ultrasonic reaction, wherein the power of the ultrasonic wave is 100 W, the reaction temperature is 45° C., and the reaction time is 5 h, and then placed in a centrifuge at 10000 rpm for 5 min, and the product obtained by centrifugation is washed three times with acetonitrile and deionized water respectively, and the obtained product is dried in a vacuum oven at 65° C. for 5 h to obtain polycyclotriphosphazene dihydroxydiphenyl sulfone microspheres; Step 2. Add a certain mass of polycyclotriphosphazene dihydroxydiphenyl sulfone microspheres into a reaction container, then add an aqueous solution of ethylene glycol, wherein the volume ratio of ethylene glycol to water is 1.5:1, place under ultrasonic dispersion for 30 minutes and then stir for 15 minutes, wherein the mass concentration of polycyclotriphosphazene dihydroxydiphenyl sulfone microspheres in the aqueous solution of ethylene glycol is 2g / L, and obtain an aqueous solution of polycyclotriphosphazene dihydroxydiphenyl sulfone ethylene glycol; then take a certain amount of 0.1mmol / L silver nitrate aqueous solution and add it to the above solution, stir for 15 minutes, then put it into a 135°C oil bath pot, and react for 5 hours under stirring conditions; then place it in a centrifuge at 10000rpm for 5 minutes, wash the product obtained by centrifugation three times with deionized water, and finally dry it in a freeze drying oven for 24 hours to obtain polycyclotriphosphazene dihydroxydiphenyl sulfone microspheres loaded with nanosilver particles.

2. A long-lasting antibacterial, thermally conductive, flame-retardant thermoplastic elastomer composite material based on TPC-ET, characterized in that: The preparation steps are as follows: Step (1): placing the linear block copolymer of polybutylene terephthalate hard segment and polybutylene glycol soft segment in a drying oven at 80° C. for 12 hours; the mass percentage of the hard segment to the soft segment in the linear block copolymer of polybutylene terephthalate hard segment and polybutylene glycol soft segment is 30:70; Step (2): 5 wt% of a nano-silver particle-loaded polycyclotriphosphazene dihydroxydiphenyl sulfone microsphere antibacterial agent, 0.5 wt% of a UV-944 light stabilizer, 0.2 wt% of an antioxidant 1010, 0.2 wt% of an antioxidant 168, and 0.3 wt% of a lubricant N,N'-ethylene bisstearamide are placed in a high-speed mixer at room temperature and stirred for 10 min to obtain a mixture A, wherein the mass percentage of the mixture A to the total weight is 6.2 wt%; 9 wt % of polysiloxane, 4.5 wt % of low melting point glass powder, 8 wt % of aluminum nitride, 8 wt % of boron nitride and 0.35 wt % of (3-aminopropyl) triethoxysilane coupling agent were placed in a high-speed mixer at 80° C. and stirred for 10 min to obtain a mixture B, wherein the mass percentage of the mixture B in the total weight was 29.85 wt %; Step (3): placing the dried linear block copolymer of polybutylene terephthalate hard segment and polybutylene glycol soft segment obtained in step (1), mixed material A and mixed material B obtained in step (2) in three weightlessness feeders respectively, setting the feeding parameters of the weightlessness feeders according to the mass percentage of the linear block copolymer of polybutylene terephthalate hard segment and polybutylene glycol soft segment: mixed material A: mixed material B = 63.95:6.2:29.85, and obtaining a long-lasting antibacterial, heat-conductive, flame-retardant thermoplastic elastomer composite material by extruding, pulling and pelletizing through a co-rotating twin-screw extruder; wherein the linear block copolymer of polybutylene terephthalate hard segment and polybutylene glycol soft segment and mixed material A are added at the main feeding port of the extruder, and mixed material B is added at the side feeding port of the extruder, the maximum setting temperature of the twin-screw extruder is 210° C., and the main screw speed is 300 rad / min; The preparation method of the polycyclotriphosphazene dihydroxydiphenyl sulfone microspheres loaded with nano-silver particles is the same as the preparation method of the polycyclotriphosphazene dihydroxydiphenyl sulfone microspheres loaded with nano-silver particles in claim 1.

3. A long-lasting antibacterial, thermally conductive, flame-retardant thermoplastic elastomer composite material based on TPC-ET, characterized in that: The preparation steps are as follows: Step (1): placing the linear block copolymer of polybutylene terephthalate hard segment and polybutylene glycol soft segment in a drying oven at 80° C. for 12 hours; the mass percentage of the hard segment to the soft segment in the linear block copolymer of polybutylene terephthalate hard segment and polybutylene glycol soft segment is 50:50; Step (2): 5 wt% of a nano-silver particle-loaded polycyclotriphosphazene dihydroxydiphenyl sulfone microsphere antibacterial agent, 0.5 wt% of a UV-944 light stabilizer, 0.2 wt% of an antioxidant 1010, 0.2 wt% of an antioxidant 168, and 0.3 wt% of a lubricant N,N'-ethylene bisstearamide are placed in a high-speed mixer at room temperature and stirred for 10 min to obtain a mixture A, wherein the mass percentage of the mixture A to the total weight is 6.2 wt%; 8 wt % of polysiloxane, 4 wt % of low melting point glass powder, 8 wt % of aluminum nitride, 8 wt % of boron nitride and 0.35 wt % of (3-aminopropyl) triethoxysilane coupling agent were placed in a high-speed mixer at 80° C. and stirred for 10 min to obtain a mixture B, wherein the mass percentage of the mixture B in the total weight is 28.35 wt %; Step (3): placing the dried linear block copolymer of polybutylene terephthalate hard segment and polybutylene glycol soft segment obtained in step (1), mixed material A and mixed material B obtained in step (2) in three weightlessness feeders respectively, setting the feeding parameters of the weightlessness feeders according to the mass percentage of the linear block copolymer of polybutylene terephthalate hard segment and polybutylene glycol soft segment: mixed material A: mixed material B = 65.45:6.2:28.35, and obtaining a long-lasting antibacterial, heat-conductive, flame-retardant thermoplastic elastomer composite material by extruding, pulling and pelletizing through a co-rotating twin-screw extruder; wherein the linear block copolymer of polybutylene terephthalate hard segment and polybutylene glycol soft segment and mixed material A are added at the main feeding port of the extruder, and mixed material B is added at the side feeding port of the extruder, the maximum setting temperature of the twin-screw extruder is 230° C., and the main screw speed is 300 rad / min; The preparation method of the polycyclotriphosphazene dihydroxydiphenyl sulfone microspheres loaded with nano-silver particles is the same as the preparation method of the polycyclotriphosphazene dihydroxydiphenyl sulfone microspheres loaded with nano-silver particles in claim 1.

4. A long-lasting antibacterial, thermally conductive, flame-retardant thermoplastic elastomer composite material based on TPC-ET, characterized in that: The preparation steps are as follows: Step (1): placing the linear block copolymer of polybutylene terephthalate hard segment and polybutylene glycol soft segment in a drying oven at 80° C. for 12 hours; the mass percentage of the hard segment to the soft segment in the linear block copolymer of polybutylene terephthalate hard segment and polybutylene glycol soft segment is 56:44; Step (2): 5 wt% of a nano-silver particle-loaded polycyclotriphosphazene dihydroxydiphenyl sulfone microsphere antibacterial agent, 0.5 wt% of a UV-944 light stabilizer, 0.2 wt% of an antioxidant 1010, 0.2 wt% of an antioxidant 168, and 0.3 wt% of a lubricant N,N'-ethylene bisstearamide are placed in a high-speed mixer at room temperature and stirred for 10 min to obtain a mixture A, wherein the mass percentage of the mixture A to the total weight is 6.2 wt%; 7 wt % of polysiloxane, 3.5 wt % of low melting point glass powder, 8 wt % of aluminum nitride, 8 wt % of boron nitride and 0.35 wt % of (3-aminopropyl) triethoxysilane coupling agent were placed in a high-speed mixer at 80° C. and stirred for 10 min to obtain a mixture B, wherein the mass percentage of the mixture B in the total weight is 26.85 wt %; Step (3): placing the dried linear block copolymer of polybutylene terephthalate hard segment and polybutylene glycol soft segment obtained in step (1), mixed material A and mixed material B obtained in step (2) in three weightlessness feeders respectively, setting the feeding parameters of the weightlessness feeders according to the mass percentage of the linear block copolymer of polybutylene terephthalate hard segment and polybutylene glycol soft segment: mixed material A: mixed material B = 66.95:6.2:26.85, and obtaining a long-lasting antibacterial, heat-conductive, flame-retardant thermoplastic elastomer composite material by extruding, pulling and pelletizing through a co-rotating twin-screw extruder; wherein the linear block copolymer of polybutylene terephthalate hard segment and polybutylene glycol soft segment and mixed material A are added at the main feeding port of the extruder, and mixed material B is added at the side feeding port of the extruder, the maximum setting temperature of the twin-screw extruder is 250° C., and the main screw speed is 300 rad / min; The preparation method of the polycyclotriphosphazene dihydroxydiphenyl sulfone microspheres loaded with nano-silver particles is the same as the preparation method of the polycyclotriphosphazene dihydroxydiphenyl sulfone microspheres loaded with nano-silver particles in claim 1.

Citation Information

Patent Citations

  • Heat conduction inflaming retarding thermoplastic polyeher ester elastomer composite and preparation method thereof

    CN102585446A

  • Thermoplastic elastomer resin composition and composite molded body

    CN104169364A